Analisis Permasalahan Kemampuan Berpikir Tingkat Tinggi Siswa SMP terkait Pembelajaran Biologi Materi Sistem Pencernaan - Mahmudah Mahmudah; Makrina Tindangen; Sonya Lumowa (Graduate School of Universitas Negeri Malang, 2018)
The problem that is often faced by students is the lack of high-level thinking ability of students especially on the material of human digestive system, causing many students who do not reach the target of graduation so that this research will be related to the problem of high-level thinking ability of junior high school students. The type of this research is quantitative with descriptive approach for data collection using questionnaire and accompanied by unstructured interview. Data analysis techniques with percentages and described. The results showed that 50% of the students were not interested, the digestive system material presented by the teachers 50% of the students were less agree, 33% of the students agreed and 16% of the students strongly agreed, the learning media used by teachers 50% of the students less agree, 33% and 16% of students strongly agreed, a similar case occurred in the use of handouts and evaluation of learning where 66% of students were less amenable and 16% of students agreed, 16% of students strongly agreed. From the results of research can be concluded that the type of device and how to teach teachers that result in the ability to think high level of junior high school students.Permasalahan yang kerap kali dihadapi oleh siswa adalah kurangnya kemampuan berpikir tingkat tinggi siswa SMP, khususnya pada materi sistem pencernaan manusia sehingga menyebabkan banyak siswa yang tidak mencapai target kelulusan sehingga penelitian ini akan berkaitan dengan permasalahan kemampuan berpikir tingkat tinggi siswa SMP. Jenis penelitian ini adalah kuantitatif dengan pendekatan deskriptif untuk pengumpulan data menggunakan angket dan disertai wawancara tidak terstruktur. Teknik analisis data dengan persentase dan dideskripsikan. Hasil penelitian menunjukkan bahwa 50% siswa tidak tertarik, materi sistem pencernaan yang disampaikan oleh guru 50% siswa kurang setuju, 33% siswa setuju dan 16% siswa sangat setuju, media pembelajaran yang digunakan oleh guru 50% siswa kurang setuju, 33% siswa setuju dan 16% siswa sangat setuju, hal yang serupa terjadi pada penggunaan handout dan evaluasi pembelajaran dimana 66% siswa kurang setuju dan 16% siswa setuju, 16% siswa sangat setuju. Dari hasil penelitian dapat disimpulkan bahwa pada jenis perangkat dan cara mengajar guru yang mengakibatkan kurangnya kemampuan berpikir tingkat tinggi siswa SMP.